2018
DOI: 10.1002/ldr.2922
|View full text |Cite
|
Sign up to set email alerts
|

Structural heterogeneity of vegetation fire ash

Abstract: Any wildfire generates ash, the solid residue derived from burning biomass. Vegetation fire ash consists of charred organic material, charcoal, and inorganic mineral substances. Recent studies identified ash deposits as a dual system: soil and ash strata. The addition of ash to the soil profile alters soil properties and dynamics. A thorough analysis of ash–soil profile reveals a structural appearance of thin laminas. The laminas differ in a variety of physical properties and mineral composition. This research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…(3) The SVC correction-the at-sensor radiance is converted into accurate reflectance by applying four stages: normalization of the albedo sequence (F1) inspected by QIs, radiometric calibration gain using the net ground-truth reflectance (F2), applying a model-based atmospheric correction (F3) using ATCOR5 model, ACORN and empirical line method, and spectral polishing using the net ground0truth reflectance (F4 C and N content in the top-ash layer was quantified. While organic C is measured using elemental analyzers, many studies, e.g., [59,65,66] reported that DR-FTIR spectroscopy yields good estimates for PyC. To quantify the area of the aromatic and aliphatic n(CH) bands, the spectra were baseline corrected in the 3200 to 2700 cm −1 region using a quartic fitting function.…”
Section: Spectral and Imagery Data Pre-processingmentioning
confidence: 99%
“…(3) The SVC correction-the at-sensor radiance is converted into accurate reflectance by applying four stages: normalization of the albedo sequence (F1) inspected by QIs, radiometric calibration gain using the net ground-truth reflectance (F2), applying a model-based atmospheric correction (F3) using ATCOR5 model, ACORN and empirical line method, and spectral polishing using the net ground0truth reflectance (F4 C and N content in the top-ash layer was quantified. While organic C is measured using elemental analyzers, many studies, e.g., [59,65,66] reported that DR-FTIR spectroscopy yields good estimates for PyC. To quantify the area of the aromatic and aliphatic n(CH) bands, the spectra were baseline corrected in the 3200 to 2700 cm −1 region using a quartic fitting function.…”
Section: Spectral and Imagery Data Pre-processingmentioning
confidence: 99%